If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 31 + -16 = 3(x + -1) Combine like terms: 31 + -16 = 15 15 = 3(x + -1) Reorder the terms: 15 = 3(-1 + x) 15 = (-1 * 3 + x * 3) 15 = (-3 + 3x) Solving 15 = -3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 15 + -3x = -3 + 3x + -3x Combine like terms: 3x + -3x = 0 15 + -3x = -3 + 0 15 + -3x = -3 Add '-15' to each side of the equation. 15 + -15 + -3x = -3 + -15 Combine like terms: 15 + -15 = 0 0 + -3x = -3 + -15 -3x = -3 + -15 Combine like terms: -3 + -15 = -18 -3x = -18 Divide each side by '-3'. x = 6 Simplifying x = 6
| cot*cos-cos=0 | | -24z^2-15z-6+3z(8z+5)=0 | | 32+2y-10=11y-14-3y | | 13(1+3b)=12b-95 | | (y+9)(y+2)=0 | | 7x-4=-2x+1+9z-5 | | x+18+3x=-9-3x-15 | | 28-4n=4(7-n)+3 | | -2-7(6v+16)=82-14 | | 7r^3+35r^2-42r=0 | | -3(4s-6)-18=-3(8s+1)-5 | | 4n+wr=r-7p | | 30=(94*0.1)+(94*x*1.8) | | 2-(x+4)=-5 | | 800+40(h-40)=1280h | | 3-(r-8)=13 | | x+(x+3)=63 | | 8x^3-x^2=12 | | x+2x+14=x+20 | | 9x+5x+2+8=4x+4+9x | | 2-(x+3)=-5 | | 8x-3(4-x)=54 | | 3h+(-7h)= | | 2w+2(3w+6)=24 | | 4=6-x^2 | | 0.5x-0.75=0.6x | | -16t^2+144t+70=390 | | 10x+2t-3w=24 | | 64s^2-81d^2= | | 2*6w=140 | | 300x-y=130 | | z^2+2z=2(z+2) |